Zero Day - Baldacci, David; McLarty, Ron.; Cassidy, Orlagh (New York : Hachette Audio, 2011)
Military investigator John Puller is called out to a remote, rural area of West Virginia to investigate the brutal murder of a family in their home. The dead husband was in the army and the wife worked for a Pentagon contractor. The local homicide detective, a woman with personal demons of her own, clashes with Puller over the investigation. What neither of them knows is what is waiting for them across the street from the murdered family's home.
Abridged.
Compact discs.
Read by Ron McLarty and Orlagh Cassidy.
Keywords: United States. -- Army Criminal Investigation Command -- Fiction; Brothers -- Fiction; Nuclear terrorism -- Fiction; Murder -- Investigation -- Fiction; Conspiracy -- Fiction; West Virginia -- Fiction; Suspense fiction; Audiobooks